From FAST to FAST-OAD: An open source framework for rapid Overall Aircraft Design. Issue 1 (January 2021) - David, Christophe; Delbecq, Scott; Defoort, Sebastien; Schmollgruber, Peter; Benard, Emmanuel; Pommier-Budinger, Valerie
Abstract: To face the increasing environmental footprint of commercial aviation, industrial and research efforts have been focusing on exploring unconventional configurations and new propulsion paradigms, mostly based on electric technology. Such explorations require Overall Aircraft Design that has to be performed in an integrated multidisciplinary design environment. Such design environments are often limited to multidisciplinary analysis, adapted for a single aircraft configuration or require an important effort to be mastered. FAST-OAD is a software program developed by ONERA and ISAE-SUPAERO for aircraft sizing analysis and optimization that aims at user friendliness and modularity. It is an aircraft sizing code based on multidisciplinary design optimization techniques and the point mass approach to estimate the required fuel and energy consumption for a given set of TLARs. This paper presents the motivations for moving from the original software program, called FAST, to the open source code FAST-OAD based on OpenMDAO.